Biotransformation of artemisinic acid by the fungus Trichothecium roseum and anti-candidal activity of its metabolites. Issue 4 (4th July 2019) - Singh, Pooja; Kapkoti, Deepak Singh; Singh, Nandan; Tewari, Rashi; Saikia, Dharmendra; Rout, Prasant Kumar; Pandey, Rakesh; Bhakuni, Rajendra Singh
Abstract: The microbial transformation of artemisinic acid(1) using cell culture of endophytic fungus Trichothecium roseum was investigated. Previously, we have reported two major metabolites, 3β-hydroxyartemisinic acid(2) and 3β, 15-dihydroxyartemisinic acid(3) from the biotransformation of artemisinic acid by the fungus T. roseum CIMAPN1. Here in the present paper, we obtained a new minor compound4 (5.2% in yield) along with compounds2 and3 through scale-up of biotransformation process of artemisinic acid using the same fungus. The structure of compound4 was established as 3-oxoartemisinic acid on the basis of its IR, ESI-MS, HRMS, 1 D ( 1 H and 13 C, DEPT), and 2 D (COSY, HSQC, HMBC) NMR spectral data analysis. The possible reaction mechanism of the formation of 3-oxoartemisinic acid from artemisinic acid was proposed. Furthermore, all the three metabolites along with the artemisinic acid were evaluated for their antifungal activity against the three fungal strains Candida albicans (ATCC 14053), Candida albicans clinical isolates and Candida kefyr (ATCC 204093). 3-Oxoartemisinic acid was the most active (4 to 16 times more potent than artemisinic acid) with MIC ranges from 125 to 500 µg/mL among all tested compounds. This study suggested that the artemisinic acid molecule has a great potential to be exploited for further biotransformation by the different fungi and can produce chemically diverse molecules with better biological activity.